A Life Dedicated to Support a Family Meal: The Women Trisikad Drivers’ Story - Villaganas, Adora A.; Giango, Wilma C.; Basubas, Elvisa O.; Villaganas, Victor (European Scientific Journal, ESJ, 2016)
The study determined the fantasies and aspirations of women trisikad drivers in Cebu City, Philippines. Specifically, the study aimed to: determine the personal profile of women trisikad drivers in Pasil, Taboan, and San Nicolas, Cebu City, examine the factors that influence their lives, extrapolate lived experiences that promote women’s decisiveness and access to economic resources. The study utilized a case study design with narrative descriptions of the primary respondents. The data generated were clustered, coded, and metaphorical themes were illuminated. Life of women trisikad drivers was dedicated to support a family meal, being a co-equal with their husbands. Living an impoverished life ‘starved like a rat’ in order to meet both ends meet. Their assertive fantasies proved that they were normal individuals who felt like: ‘a superwoman that finds her way out at the end of the tunnel’, empowered and took control over scarce resources, ‘a blooming lily under the 49 degrees heat of a tropical summer’, struggled poverty, and ‘a mother hen protecting their chicks from a gliding skyline hawk’, raised an income for children’s survival. Their life-changing aspirations included: ‘chasing ice castles in the air’, never met the normal Cindrella life syndrome, ‘buoyant force that makes the boat sail to its final destination, with their husbands as the propeller’, gained support by their husbands, and ‘newly hibernated amphibians in a hostile ecosystem’, despised the strain of gender stereotyping. Their lived experiences characterized in ‘painful joy’ because of their minimal income, ‘serving as an army of ants’, chased equally with their male counterparts just to bring food on the table, and ‘being the winds beneath their husbands’ wings’, assured by their husbands’ love and protection. Though, their economic status is a ‘scratching and pecking condition’, earned typically in day-to-day subsistence with hope.